Biochemical properties and progress in cancers of tRNA‐derived fragments. Issue 3 (31st October 2019) - Ma, Zhongliang; Zhou, Jinbao; Shao, Yang; Jafari, Fatemah.A.; Qi, Pengfei; Li, Yanli
Abstract: tRNA‐derived small RNAs (tRFs), a kind of noncoding RNAs, are generated from transfer RNAs. tRFs have some types according to their source and sizes. They play important roles in cell life and carcinogenesis. In this paper, we review the biogenesis and biological properties. We also focus on current progress of tRFs and some tsRNAs such as tRF‐Leu‐CAG, which have been studied or will be further investigated in tumorgenesis and diagnostic biomarkers in the clinic. Abstract : Cleavage by Dicer takes place in the cytoplasm, and tRNA molecules must be imported there from the nucleus. This transport may occur at different stages of tRNA maturation: misfolded, properly folded but not aminoacylated, or fully mature.